Heat of fusion of polymer crystals by fast scanning calorimetry. (22nd September 2017) - Cebe, Peggy; Thomas, David; Merfeld, John; Partlow, Benjamin P.; Kaplan, David L.; Alamo, Rufina G.; Wurm, Andreas; Zhuravlev, Evgeny; Schick, Christoph
Abstract: Knowledge of the specific equilibrium heat of fusion of polymer crystals, Δ h f 0 [J/g], is an essential thermal property of polymers which permits the degree of crystallinity to be obtained from thermal measurements. We describe an approach to evaluate Δ h f 0 ( T m ) and implement this method using fast scanning calorimetry (FSC). Our method uses the measured enthalpy of melting plotted against the product of the sample mass times its crystallinity for samples with variable masses and/or crystallinities. Then, Δ h f 0 is obtained from the slope of the entire data set, reducing errors in the measurement. To demonstrate the method and give proof of principle, we measure Δ h f 0 ( T m ) of samples of a narrow fraction of linear polyethylene (PE) with a weight average molecular weight of 60, 700 g/mol, whose thermal properties are already known in the literature. For PE, we obtain Δ h f 0 (PE) = (281 ± 6) J/g at T m  = 136 °C, in close agreement with literature values. Then, we apply the method to determine Δ h f 0 ( T m ) of silk fibroin, a fibrous protein, yielding a first estimate of the heat of fusion of silk crystals, Δ h f 0 (Silk) ∼ (137 ± 7) J/g. Advantages include: reduction of error, applicability to all types of polymers, copolymers, and blends regardless of degree of crystallinity, and applicability to biomaterials which may require fast scanning rates of FSC to prevent degradation. Graphical abstract: Highlights: A method for determining the heat of fusion of polymer crystals, Δhf 0, is proposed. The method plots endotherm area vs. (mass x crystallinity). Δhf 0 is the slope. Fast scanning calorimetry is used to demonstrate the method on polyethylene, PE. We find Δhf 0  = (281 ± 6) J/g for PE, and is within 2% of its literature value. For the biopolymer, silk fibroin, containing beta sheet crystals, Δhf 0  = (137 ± 7) J/g.